Relationship between ground reaction force and attack time according to the position of hand segments during counter attack in Kendo - Hyun, S. H.; Jin, H. S.; Ryew, C. C. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to analyze the relationship between ground reaction force (GRF) and attack time according to the position of hand segments during counter attack in Kendo. Method: The participants consisted of 10 kendo athletes (mean age: 21.50±1.95 yr, mean height: 175.58±5.02 cm, mean body weight: 70.96±9.47 kg) who performed standard head strikes (A) and counter attack with a preferred hand position of +10 cm (B), 0 cm (C), and -10 cm (D). One force-plate (AMTI-OR-7., USA) was used to collect GRF data at a sample rate of 1,000 Hz. The variables analyzed were the attack time, medial-lateral GRF, anterior-posterior GRF (AP GRF), peak vertical force (PVF), and loading rate. Results: The total attack time was shorter in types A and C than in types C and D. The AP GRF, PVF, and loading rate had significantly higher forces in types C and D than in types A and C. The attack time (bilateral and unilateral leg support and total) was positively correlated with the GRF variables (vertical GRF and loading rate) during the counter attack in Kendo (r = 0.779 [R2=0.607], p < 0.001). Conclusion: The positions of the hand segments can be changed by various conditions of the opponent in Kendo competitions; however, the position preferred by an individual can promote the successful ratio of the counter attack.